Improving hydrocarbon toxicity tolerance in poultry: role of genes and antioxidants - Oleforuh-Okoleh, Vivian U.; Sikiru, Akeem B.; Kakulu, Iyenemi I.; Fakae, Barineme B.; Obianwuna, Uchechukwu E.; Shoyombo, Ayoola J.; Adeolu, Adewale I.; Ollor, Ollor A.; Emeka, Onyinyechi C. (Frontiers in Genetics, 2023)
Sustenance of smallholder poultry production as an alternative source of food security and income is imperative in communities exposed to hydrocarbon pollution. Exposure to hydrocarbon pollutants causes disruption of homeostasis, thereby compromising the genetic potential of the birds. Oxidative stress-mediated dysfunction of the cellular membrane is a contributing factor in the mechanism of hydrocarbon toxicity. Epidemiological studies show that tolerance to hydrocarbon exposure may be caused by the activation of genes that control disease defense pathways like aryl hydrocarbon receptor (AhR) and nuclear factor erythroid 2p45-related factor 2 (Nrf2). The disparity in the mechanism and level of tolerance to hydrocarbon fragments among species may exist and may result in variations in gene expression within individuals of the same species upon exposure. Genomic variability is critical for adaptation and serves as a survival mechanism in response to environmental pollutants. Understanding the interplay of diverse genetic mechanisms in relation to environmental influences is important for exploiting the differences in various genetic variants. Protection against pollutant-induced physiological responses using dietary antioxidants can mitigate homeostasis disruptions. Such intervention may initiate epigenetic modulation relevant to gene expression of hydrocarbon tolerance,